Changes in maxillary perfusion following Le Fort I osteotomy in orthognathic surgery - Sancar, Bahadir; Unluturk, Burak; Musulluoglu, Ferhat (Annals of Medical Research, 2021)
None
Keywords: Le Fort I osteotomy; maxilla; perfusion